Cost-effectiveness of behavioural counselling intervention compared with non-intervention for adult patients with metabolic syndrome to prevent cardiovascular diseases and type 2 diabetes in Japan: a microsimulation modelling study - Yoko M Nakao; Rei Goto; Yoko Akune; Hisataka Anezaki (BMJ Open, 2024)
Objectives Nationwide lifestyle intervention—specific health guidance (SHG) in Japan—employs counselling and education to change unhealthy behaviours that contribute to metabolic syndrome, especially obesity or abdominal obesity. We aimed to perform a model-based economic evaluation of SHG in a low participation rate setting.Design A hypothetical population, comprised 50 000 Japanese aged 40 years who met the criteria of the SHG, used a microsimulation using the Markov model to evaluate SHG’s cost-effectiveness compared with non-SHG. This hypothetical population was simulated over a 35-year time horizon.Setting SHG is conducted annually by all Japanese insurers.Outcome measures Model parameters, such as costs and health outcomes (including quality-adjusted life-years, QALYs), were based on existing literature. Incremental cost-effectiveness ratios were estimated from the healthcare payer’s perspective. Deterministic and probabilistic sensitivity analyses (PSA) were conducted to evaluate the uncertainty around the model input parameters.Results The simulation revealed that the total costs per person in the SHG group decreased by JPY53 014 (US$480) compared with that in the non-SHG group, and the QALYs increased by 0.044, wherein SHG was considered the dominant strategy despite the low participation rates. PSA indicated that the credibility intervals (2.5th–97.5th percentile) of the incremental costs and the incremental QALYs with the SHG group compared with the non-SHG group were −JPY687 376 to JPY85 197 (−US$6226 to US$772) and −0.009 to 0.350 QALYs, respectively. Each scenario analysis indicated that programmes for improving both blood pressure and blood glucose levels among other risk factors for metabolic syndrome are essential for improving cost-effectiveness.Conclusions This study suggests that even small effects of counselling and education on behavioural modification may lead to the prevention of acute life-threatening events and chronic diseases, in addition to the reduction of medication resulting from metabolic syndrome, which results in cost savings.